Evolution of some components of agroecosystems productivity from Vinga Plain in water stress situations - Dicu, Daniel; Borza, Iacob; Tarau, Dorin (Acta Agraria Debreceniensis, 2010)
The researches are inscribed on line of substantiation of durable agricultural system, having main objective the prominence ofquantitative and qualitative modifications made on agro-system level under the effect of no-tillage system for wheat, maize and soybeans.The experimental field is placed on a cambium chernozem, with a medium content of clay, dominant in the Prodagro West Arad agrocentreand representative for a large surface in the Banat-Crisana Plain.The passing to no-till system change the structure of technological elements, through less soil works, so the impact on agro-system isdifferent comparing with conventional tillage, first less the intervention pressure on agro-system ant secondly appears new interactions, newequilibriums and disequilibriums.Considering the evolution of soil humidity, the observations made monthly (by taking soil samples and laboratory determinations) forthe three cultures showed that in the no-till system, there are more uniform values in the soil profile, and in the variants where the deep workof soil was made it could be observed a low increase of the water volume in the soil.